The lamellar-to-isotropic transition in ternary amphiphilic systems - Schwarz, Ulrich S.; Swamy, K.; Gompper, Gerhard (Arxiv, 1996)
We study the dependence of the phase behavior of ternary amphiphilic systems on composition and temperature. Our analysis is based on a curvature elastic model of the surfactant film with sufficiently large spontaneous curvature and sufficiently negative saddle-splay modulus that the stable phases are the lamellar phase and a droplet microemulsion. In addition to the curvature energy, we consider the contributions to the free energy of the long-ranged van der Waals interaction and of the undulation modes. We find that for bending rigidities of order k_B T, the lamellar phase extends further and further into the water apex of the phase diagram as the phase inversion temperature is approached, in good agreement with experimental results.